#### Answer

$\pm 6$

#### Work Step by Step

$\log _{3}\left( x^{2}-g\right) =3\Rightarrow x^{2}-g=3^{3}\Rightarrow x^{2}=3^{3}+9=36\Rightarrow x=\pm \sqrt {36}=\pm 6$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$\pm 6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.